Stambul Comedy Exploration in Early 20th-Century Semarang: Meaningful Teaching about Colonialism - Amin, Syaiful; Sariyatun, Sariyatun; Gunarhadi, Gunarhadi; Purwanta, Hieronymus (Harmonia: Journal of Arts Research and Education, 2024)
This study aims to analyze the results of exploring stambul comedy as part of Indies art in early 20th-century Semarang as an effort to implement meaningful learning about colonialism for students. This research was conducted using a qualitative framework with a case study approach. Data were collected through interviews, observations, and document studies. The data analysis for this research referred to Yin’s two patterns: pattern matching and explanation building. The results showed that the narrative of Stambul comedy in early 20th-century Semarang is relevant for developing students’ knowledge about colonialism in a more contextual manner. Findings indicate that students’ initial understanding of colonialism was still not contextual and tended to be theoretical, with colonialism merely understood as a process of occupation and domination by one nation over another. After exploring material on the development of Indies art through contextual teaching and learning, students were able to think critically and collaboratively. A constructivist process could trigger acceptance and rejection of colonialism: discovering, elaborating, and determining the meaning of learning. Moreover, students’ new knowledge could be factually constructed, influenced by factors such as reading preferences, collaborative abilities, and critical examination of texts provided by the teacher and further explored by the students.